Resilience scientists as change-makers—Growing the middle ground between science and advocacy?. Issue 53 (November 2015) - Milkoreit, Manjana; Moore, Michele-Lee; Schoon, Michael; Meek, Chanda L.
Highlights: We review debates about the role of scientists in policy-making processes, focusing on resilience science. Resilience science makes important value commitments based on its systems ontology. Resilience scholars should be aware of risks and benefits associated with their scientific practice. We encourage an explicit debate among resilience scholars about their role in policy processes. Abstract: Since the beginning of the 20th century, the understanding of the relationship between science and policy making has altered significantly from one that separated the 'truth seeking' domain of science to one characterized by an increasingly close integration of science into the domain of politics, complete with contested values and opinions. Resilience scientists have only recently entered this discussion, but a coherent approach to purposeful institutional change and policy remains elusive, despite core theoretical concepts focusing on the scale and 'fit' of governance institutions for complex social–ecological systems. While the appropriateness of value-driven science is highly contested across all scientific fields, this paper argues that articulating a coherent position is of particular relevance for resilience scientists and others, who use a theoretical framework that is infused with a specific value-set, such as ecosystem and species protection, conservation, inclusiveness and participatory governance processes. Outlining both the challenges of navigating the science–policy interface and a set of approaches resilience scientists could take in response to these challenges, we seek to initiate reflection and debate within the resilience science community concerning their own role in growing the middle ground between science and politics, and conducting science within that hybrid space.